Penguatan Pusat Laboratorium Forensik Bareskrim Polri dalam Reformasi Pembuktian Pidana Berbasis Scientific Crime Investigation - Sudjarwoko Sudjarwoko; Anthon F. Susanto (Mahesa Research Center, 2026)
The development of conventional, digital, and transnational crimes requires a criminal evidence system capable of integrating scientific evidence in an objective, accurate, and accountable manner. The Forensic Laboratory Center of the Indonesian National Police Criminal Investigation Agency plays a strategic role in supporting Scientific Crime Investigation (SCI). However, existing discussions of forensic laboratories tend to position them primarily as technical instruments of criminal investigation and have not sufficiently integrated evidentiary, institutional, and legal reform perspectives. This study aims to analyze the role of the Forensic Laboratory Center of the Indonesian National Police Criminal Investigation Agency in strengthening scientific evidence-based criminal proceedings and to formulate directions for strengthening forensic institutions within the reform of the Indonesian criminal evidence system. This study employs a normative juridical method with a descriptive-analytical approach. The research materials consist of legislation, scientific literature, previous studies, and relevant documents, supported by interviews with personnel possessing expertise in forensic science. The analysis examines the relationship between criminal evidence law, forensic science, and the implementation of SCI from investigation and inquiry to judicial proof. The findings demonstrate that the Forensic Laboratory Center plays a strategic role through five major forensic service areas: documents, printed products, and counterfeit money; ballistics and metallurgy; physics and computer forensics; chemistry, toxicology, and biology; and narcotics and controlled substances. The integration of these services strengthens the use of scientific evidence in identifying, analyzing, and validating evidence while reducing dependence on subjective forms of proof. The novelty of this study lies in positioning the strengthening of the Forensic Laboratory Center as an integral component of criminal evidence reform based on SCI rather than merely as a technical support function for investigation. This study contributes to criminal law policy by emphasizing the need to strengthen forensic regulations, institutional capacity, human resources, and forensic technologies to establish a more objective, accountable, and scientifically validated criminal evidence system.